Fungal infection and neurodevelopmental outcomes at 18–30 months in preterm infants - Zhou, Qi; Kelly, Edmond; Luu, Thuy Mai; Ye, Xiang Y.; Ting, Joseph; Shah, Prakesh S.; Lee, Shoo K. (Frontiers in Pediatrics, 2023)
Background Invasive fungal infection (IFI) is associated with significant mortality and morbidity among preterm infants but there has been no population-based study of long-term neurodevelopmental outcomes. The objective of this study was to examine population-based incidence trends as well as mortality, short term in-hospital morbidity and long-term neurodevelopmental outcomes among preterm infants with IFI, non-fungal infections (NFI) and no infections in Canada. Methods We conducted a retrospective cohort study of 8408 infants born at <29 weeks gestational age (GA), admitted to Canadian Neonatal Network neonatal intensive care units (NICU) from April 2009 to Dec 2017, and followed up at 18-30 months corrected age (CA) in Canadian Neonatal Follow-Up Network clinics. We compared mortality, long term neurodevelopmental outcomes and short term in-hospital morbidity among 3 groups of infants (IFI, NFI, and no infections). Results The incidence of IFI was 1.3%, non-IFI 26.9% and no infections 71.7%. IFI incidence varied between 0.93-1.94% across the study period with no significant trend over time. Infants of higher gestational age were significantly (p<0.01) less likely to have IFI. Among infants with IFI, NFI and no infections, the incidence of the significant neurodevelopmental impairment (sNDI) was 44.26%, 21.63% and 14.84% respectively, while mortality was 50%, 25.35% and 22.25% respectively. Even after risk adjustment for confounders (GA, Score for Neonatal Acute Physiology Version II, ruptured membranes >24 hours, maternal antibiotic treatment, antenatal steroid use, cesarean section), infants with IFI had significantly higher odds of sNDI than NFI (aOR 2.19; 95%CI1.23,3.91) or no infections (aOR 2.97; 95% CI 1.55,5.71), and higher odds of mortality than NFI (aOR 1.55; 95% CI 1.07,2.26) or no infections (aOR 1.45; 95%CI 0.97,2.17). Conclusions Preterm infants with invasive fungal infections have significantly higher incidence of mortality and adverse neurodevelopmental outcomes than those with non-invasive fungal infections and no infections.